KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DI PROVINSI JAMBI: Studi Multi Kasus pada MAN Olak Kemang Kota Jambi, MAN Pulau Temiang Kabupaten Tebo, dan MAN 2 Kabupaten Tanjung Jabung Timur - Sumarto Sumarto (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
The objective of this study was to find out why the transformational headmaster can instill islamic school culture, the role of transformational leadership and the success of transformational leadership role in instilling islamic shool culture in province of Jambi. The approach used in this study is a qualitative descriptive ap-proach. Data collection techniques using observation, interviews and documenta-tion. Analysis of the data using the model of Miles and Huberman. Research re-sult; Principals have a muslim personality as Prophet, know the needs of his staff, build his staff confidence, building a shared commitment to make the shift to-wards change for the better, creative, productive and innovative, exemplary and courage to face challenges, sensitive to complaints and suggestions of staff, deli-beration and spirit of motivation. Principal transformational leadership roles are as Direction Setter, Agent of Change, Spokesperson, Coach, support-getter, suc-ces-guarantor and path-finder.